1996
DOI: 10.1021/bi9616458
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc Binding Site in Viral Serine Proteinases

Abstract: The NS3 protein of hepatitis C virus contains a chymotrypsin-like serine proteinase domain. We built a homology model of this domain which predicts the presence of a tetradentate metal binding site formed by three cysteines and one histidine. These residues are strictly conserved in all known hepatitis C viral genotypes as well as in other recently discovered related hepatitis viruses. We show that the hepatitis C virus enzyme does indeed contain a Zn2+ ion with S3N ligation and that the metal is required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 37 publications
(43 reference statements)
3
69
0
1
Order By: Relevance
“…Disulphide bridges present in these extracellular serine proteinases are unlikely to be stable in the reducing intracellular milieu. Since NS3 is an intracellular proteinase, we proposed that the zinc-binding site is used to stabilise the relative orientation of the two b-barrel domains, thus indirectly in¯uencing the position of the catalytic triad, which is located in the crevice between the domains (De Francesco et al, 1996). However, we observe also that the histidine residue is highly conserved in all the HCV strains and HCV-related viruses.…”
Section: The Zn-binding Sitementioning
confidence: 69%
“…Disulphide bridges present in these extracellular serine proteinases are unlikely to be stable in the reducing intracellular milieu. Since NS3 is an intracellular proteinase, we proposed that the zinc-binding site is used to stabilise the relative orientation of the two b-barrel domains, thus indirectly in¯uencing the position of the catalytic triad, which is located in the crevice between the domains (De Francesco et al, 1996). However, we observe also that the histidine residue is highly conserved in all the HCV strains and HCV-related viruses.…”
Section: The Zn-binding Sitementioning
confidence: 69%
“…A previous study has revealed that a zinc ion is required for the structural integrity and activity of the NS3 protease (DeFrancesco et al, 1996). An electron density above the 4cr level is seen in the MIR map between the F1/A2 and D2/E2 loops.…”
Section: Overall Three-dimensional Structurementioning
confidence: 81%
“…Comparison of the NS3 protease structures in the presence and in the absence of NS4A suggested that NS4A stabilizes the N-terminal domain of the protease, thus optimizing the orientation of the catalytic triad. A characteristic feature of NS3 is the presence of a structural zinc ion that is coordinated tetrahedrally by three cysteines and a histidine residue at a site located opposite the active site (12,20,35,51). Though the NS3 protease domain is covalently attached to an RNA helicase possessing ATPase activity, the helicase domain is not required for optimal protease activity.…”
mentioning
confidence: 99%